Immunohistochemical based molecular subtypes of muscle-invasive bladder cancer: association with HER2 and EGFR alterations, neoadjuvant chemotherapy response and survival - Duaa S. Helal; Sara A. Darwish; Radwa A. Awad; Dina A. Ali; Dina M. El-Guindy (BMC, 2023)
Abstract Muscle-invasive bladder cancers (MIBCs) is a group of molecularly heterogonous diseases that could be stratified into subtypes with distinct clinical courses and sensitivities to chemotherapy. Clinical application of molecular subtypes could help in prediction of neoadjuvant chemotherapy (NAC) responders. Immunohistochemical (IHC) markers such as GATA3, cytokeratin (CK) 5/6, and p53 are associated with these subtypes and are widely available. Human epidermal growth factor receptor 2 (HER2) and epidermal growth factor receptor (EGFR) are mutated in multiple cancers including MIBC and are potential therapeutic targets. HER2/EGFR status of MIBC subtypes has not been investigated. Tissue microarrays (TMAs) were constructed from transurethral resection of the bladder tumor (TURB) specimens and stained with GATA3,CK5/6,p53 and HER2 in addition to Quantitative Reverse Transcription PCR for detection of EGFR gene. Of the total cases, 45% were luminal, 36.7% basal and 18.3% p53 wild subtype (p53-WT). Univariate analysis showed that overall survival (OS) and disease-free progression survival (DFS) were significantly longer for luminal subtype. In multivariate analysis, molecular subtype, HER2 status and LV invasion were independent prognostic factors for DFS and OS. Basal subtype showed a significantly better response to NAC. HER2 expression was significantly higher in luminal while EGFR expression was significantly higher in basal subtype. Kaplan-Meier survival curves revealed a significant longer OS and DFS for HER2 negative than positive cases. MIBC can be stratified using a simple IHC panel [GATA3,CK5/6,P53] into clinically relevant prognostic molecular subtypes. Basal tumors are aggressive and respond well to NAC while luminal have better OS. P53-WT tumors are chemoresistant and require further treatments. HER2 and EGFR are potential therapeutic targets for molecular subtypes of MIBC where luminal tumors are more likely to benefit from HER2 and basal from EGFR directed therapies.